Phytochemical and in-vitro antimicrobial screening of Sanseviera liberica Gérôme and Labroy (Agavaceae) root extract - GAE Asika; L Okunrobo; F Anowi; B Udeh (Journal of Applied Sciences and Environmental Management, 2014)
Sanseviera liberica is used in Nigerian folk medicine for the treatment of asthma, abdominal pain, diarrhea, wounds of the foot, gonorrhea, snake bites etc. Some of these diseases are caused by pathogenic bacteria. To validate the trado-medical applications of S. liberica, an investigation of the phytochemical and antimicrobial properties of the methanol and n – hexane extracts was conducted. Phytochemical screening revealed the presence of tannins, flavonoids, saponins, reducing sugars and   carbohydrates in both extracts. Alkaloids were present only in the methanol extract. Glycosides, terpenoids and steroids were absent in both extracts. The proximate analysis of S. liberica showed total ash value of 6.0 %, acid insoluble ash of 1.10 %, alcohol extractive value of 6.80 %, water  extractive value of 5.20 % and moisture content of 14.50 %.The broth microdilution technique was used to evaluate the antimicrobial activities of both the methanol and n – hexane extracts of S. liberica. Results showed that Psuedomonas. aureginosa, Streptococci pyrognase and Staphylococcus aureus were sensitive to the methanol extract while Candida albicans,  Klebsiella pneumonia, Salmonella typhii, Baccilus subtilis and Escherischia coli were not sensitive. All the eight microorganisms involved in the  antimicrobial assay were not sensitive to the n-hexane extract. © JASEM